Efektivitas Strategi Think Pair Share terhadap Hasil Belajar Matematika Materi Pokok Persamaan Kuadrat di Kelas X SMA Negeri 5 Padangsidimpuan - Nisah Ayu Siregar; Yola Putri Anggraini (Lembaga Yasin AlSys, 2026)
Research on cooperative learning strategies has been widely conducted; however, studies that specifically examine the effectiveness of the Think-Pair-Share strategy in teaching quadratic equations in senior high school mathematics remain limited. This study aims to analyze the effect of the effectiveness of the Think-Pair-Share instructional strategy on mathematics learning outcomes for the topic of quadratic equations among Grade X students at SMA Negeri 5 Padangsidimpuan. The research employed a quantitative approach with a correlational design, involving a sample of 102 students selected through simple random sampling. Data were collected using a questionnaire to measure the implementation of the Think-Pair-Share strategy and a multiple-choice objective test to measure mathematics learning outcomes. Data analysis was conducted descriptively and inferentially using normality tests, Pearson Product Moment correlation, and t-tests at a 5% significance level. The results show that the implementation of the Think-Pair-Share strategy was in the “good” to “very good” category, while students’ mathematics learning outcomes were in the “fair” to “good” category. Inferential analysis indicates a significant relationship between the Think-Pair-Share learning strategy and mathematics learning outcomes on quadratic equations. These findings reinforce cooperative learning theory, which emphasizes student activity and interaction, and confirm that the Think-Pair-Share strategy is effective for improving mathematics learning outcomes on quadratic equations at the senior high school level.